INVESTIGATION OF COLLABORATIVE INTERACTION USING INTERACTIVE TABLE-BASED SETTING VERSUS COMPUTER-BASED SETTING - PUCKDEEPUN, THAWANRAT (2012)
Nowadays technologies are available in classroom for teaching and learning. Desktop computer offers multimedia resources that support student’s learning in their academic activity. However, this technology does not effectively support collaborative activity while using a single computer. Recent technologies of interactive whiteboard (IWB) or tabletop have overcome this problem. A big interactive screen with multimedia resources offers collaborative interaction which allows the users to control applications by directly touching on the screen. In vice versa, while using desktop computer, mouse need to be used by scrolling on flat surface to control cursor which is not interactive. Even thought IWB or tabletop has multi functions to support collaborative activity, the main problem is too expensive and can not be afforded by budget schools. Therefore, the aim of this research study is to propose a new design of low-cost interactive table (ITB) and IR devices. At the same time evaluate effectiveness of ITB and IR devices. ITB provides a big interactive screen which has ability to support any multimedia applications which controlling by cursor.